2020
DOI: 10.36688/imej.3.137-143
|View full text |Cite
|
Sign up to set email alerts
|

Array modeling and testing of fixed OWC type Wave Energy Converters

Abstract: If wave energy technology is to mature to commercial success, array optimization could play a key role in that process. This paper outlines physical and numerical modeling of an array of five oscillating water column wave energy converters. Numerical model simulations are compared with experimental tank test data for a non-optimal and optimal array layout. Results show a max increase of 12% in average power for regular waves, and 7% for irregular waves between the non-optimized and optimized layouts. The numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In recent works by [800,798,799] and [62], wave propagation models have been coupled to BEM software, in the latter case to study the wave-structure interaction in a wave farm consisting of two clusters, or subgroups. Examples of wave farm studies based on BEM for resolving hydrodynamic interactions can be found in [559,719,755,680,62,80,470].…”
Section: Numerical Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent works by [800,798,799] and [62], wave propagation models have been coupled to BEM software, in the latter case to study the wave-structure interaction in a wave farm consisting of two clusters, or subgroups. Examples of wave farm studies based on BEM for resolving hydrodynamic interactions can be found in [559,719,755,680,62,80,470].…”
Section: Numerical Modellingmentioning
confidence: 99%
“…Results from the numerical software WEC-Sim were compared with experimental data from five pitching WaveStar WECs in a staggered layout in [491]. An array of five OWCs was studied in the time domain by [80] using the open-source software WEC-Sim, and the same software was used by [491] to study an array of five pitching WaveStar devices in the time-domain. Similarly, WEC-Sim was coupled to NEMOH and used to study a 5-WEC array by [61].…”
Section: Solving the Equations Of Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Bosma [121], who outlined numerical and physical array testing, optimized and non-optimized layouts with 5 OWCs were considered. The results showed that when the layout is optimized, the average power in regular and irregular waves increased by 12% and 7%, respectively.…”
Section: Layout Configurationmentioning
confidence: 99%
“…da Fonseca et al [3] studied a triangular array of three spar-buoy WECs in scale 1:32, and it was observed that the interaction factor was larger than 1 in wave climates with large energy periods. Five fixed OWCs deployed in two different layouts (chosen based on earlier layout optimization) were studied experimentally and numerically by Bosma et al [7], both in regular and irregular waves: a maximal power increase of 12% was found between the non-optimal and the optimal layout. In Mackay et al [8], an array consisting of four Wavebob models at scale 1:19 was studied experimentally and compared to a numerical time-domain model.…”
Section: Introductionmentioning
confidence: 99%